The dialectical behavior therapy skills workbook : practical DBT exercises for learning mindfulness, interpersonal effectiveness, emotion regulation - McKay, Matthew; Wood, Jeffrey C.; Brantley, Jeffrey (New Harbinger self-help workbook., 2019)
"A clear and effective approach to learning evidence-based DBT skills--now in a fully revised and updated second edition. Do you have trouble managing your emotions? First developed by Marsha M. Linehan for treating borderline personality disorder, dialectical behavior therapy (DBT) has proven effective as treatment for a range of other mental health problems, and can greatly improve your ability to handle distress without losing control and acting destructively. However, to make use of these techniques, you need to build skills in four key areas: distress tolerance, mindfulness, emotion regulation, and interpersonal effectiveness. The Dialectical Behavior Therapy Skills Workbook, a collaborative effort from three esteemed authors, offers evidence-based, step-by-step exercises for learning these concepts and putting them to work for real and lasting change. Start by working on the introductory exercises and, after making progress, move on to the advanced-skills chapters. Whether you're a mental health professional or a general reader, you'll benefit from this clear and practical guide to better managing your emotions. This fully revised and updated second edition also includes new chapters on cognitive rehearsal, distress tolerance, and self-compassion. Once you've completed the exercises in this book and are ready to move on to the next level, check out the authors' new book, The New Happiness Workbook. This book has been awarded The Association for Behavioral and Cognitive Therapies Self-Help Seal of Merit -- an award bestowed on outstanding self-help books that are consistent with cognitive behavioral therapy (CBT) principles and that incorporate scientifically tested strategies for overcoming mental health difficulties. Used alone or in conjunction with therapy, our books offer powerful tools readers can use to jump-start changes in their lives. Find more help online at elearning.newharbinger.com. New Harbinger Online Learning offers web-based treatment for borderline personality disorder (BPD) and emotion dysregulation based on the book The Dialectical Behavior Therapy Skills Workbook. Other New Harbinger Online Learning modules offer treatment for stress, anxiety, depression, and anger"--